Engaging with the future: framings of adaptation to climate change in conservation - Munera Roldan, C.; Colloff, Matthew J.; Locatelli, Bruno; Wyborn, C. (Informa UK Limited, 2022)
The term ‘adaptation’ is commonplace in conservation research and practice, but often without a reflection on the assumptions, expectations, or frames of reference used to define goals and actions. Communities of practice (e.g. conservation researchers, protected areas managers) have different interpretations of climate change impacts on biodiversity and different ways of defining, operationalizing and implementing adaptation. Their cognitive and motivational expectations for the future are associated with different paths to reach such desired futures. To understand how adaptation is framed in conservation, we undertook a systematic review with a thematic synthesis of the definitions of the term as used in the academic conservation literature. From a sample of 150 articles, only 36 provided a definition of adaptation. We critically appraised the explicit definitions to identify emergent themes that represent particular adaptation approaches. Themes were then grouped, and each group was assigned to a scholarly tradition, onto-epistemological approach and theoretical perspective. Based on theoretical perspectives on social change, we propose a framework (including individual cognitive basis, social interactions, and openness to alternatives) to analyse how change is framed in the definitions and how the framings influence adaptation options. The grouped themes represent passive, active, or indirect adaptation approaches. We used these themes to generate a conceptual model to guide conservation researchers and practitioners engaged in climate adaptation research, policy and management to aid reflection and understanding of the options available to design adaptation agendas and allow negotiation of diverse interests, views and expectations about the future.